Virtual R&D teams: a sustainable infrastructure for promoting SMEs - Ale Ebrahim, N.; Ahmed, S.; Taha , Z. (2008)
small and medium sized enterprises (SMEs) are a major part of the industrial economies. Their survival and growth has therefore been a prominent issue. Research and development (R&D) enables firms to create new technologies and/or to build on existing technologies obtained through technology transfer. Nowadays unpredictable environment suggests that many firms seek new ways of conducting their business through some kind of R&D activities to make a profit and stay ahead of the competition. To survive in the global economy SMEs have to improve their products and processes exploiting their intellectual capital in a dynamic network of knowledge-intensive relations inside and outside their borders. SMEs need to focus on core competences for efficiency matters; they need to cooperate with external partners to compensate for other competences and resources. Responding to the increasing de-centralization and globalization of work processes, many SMEs have responded to their dynamic environments by introducing virtual teams. Virtual teams are growing in popularity. By a comprehensive literature review this article following define a virtual teams, SMEs and its characteristics, addressing a sustainable infrastructure for promoting SMEs. Finally conclude that managers of SMEs should invest less in tangible assets, but more in the areas of expanding virtual R&D activities which will directly generate their future competitive advantage. Future research need to elaborate the effect of virtual R&D team working on the performance of SMEs.